AKSES KEADILAN BAGI HAK PENYANDANG DISABILITAS BERHADAPAN DENGAN HUKUM (Studi pada Pengadilan Negeri Padang dan Wonosari) - Heryansyah, Despan; Marzuki, Suparman (JOURNAL EQUITABLE, 2024)
Constitutional amendments that accommodate various rights are the starting point for a new era of human rights in Indonesia, including for people with disabilities. Along the way, the Indonesian government has also responsively ratified the Convention on the Rights of Persons With Disabilities (CRPD) into Law Number 19 of 2011, Law Number 8 of 2016 concerning Persons with Disabilities, and PP Number 39 of 2020 concerning Adequate Accommodation for Persons with Disabilities in Judicial Process. Departing from the two contexts above, namely the weak protection of access to justice for people with disabilities and the fairly complete normative guarantee of the right to justice for people with disabilities, the author looks at the further implications for practice in the District Court. Apart from that, the author also analyzes the problems faced by the District Court in providing access to justice, by using the Padang District Court and the Wonosari District Court as research objects. The research results show that to this day, people with disabilities still encounter many obstacles in gaining access to justice. These obstacles are encountered both in terms of regulations, human resources, and facilities and infrastructure. A comparison of the fulfillment of access to justice for persons with disabilities between the Padang District Court and the Wonosari District Court gives rise to quite a sharp gap because it is influenced by at least three factors, namely: the perspective of the Chief of Justice, support from civil society organizations, and support from universities.